Humoral and Cellular Immune Response After a 3-Dose Heterologous SARS-CoV-2 Vaccination Using the mRNA-BNT162b2 and Viral Vector Ad26COVS1 Vaccine in Hemodialysis Patients - Davidovic, Tamara; Schimpf, Judith; Abbassi-Nik, Armin; Stockinger, Richard; Sprenger-Mähr, Hannelore; Lhotta, Karl; Zitt, Emanuel (Frontiers in Immunology, 2022)
Background Due to the waning humoral response after a two-dose SARS-CoV-2 mRNA vaccination, a third booster was recommended in hemodialyis patients. Data on a heterologous mRNA-vector regimen, which might improve immunogenicity, are very limited. Methods In this observational study 36 chronic hemodialysis patients (mean (SD) age 66.9 (15.9) years, 33.3% females) were followed up for 13 months. All patients were vaccinated twice using the mRNA-BNT162b2 vaccine, followed by a 3rd dose of the vector vaccine Ad26COVS1 eight months later. We assessed the humoral response by quantifying the anti-SARS-CoV-2 spike IgG antibody and neutralizing antibody concentrations. The cellular immune response was evaluated via SARS-CoV-2 spike protein-specific interferon-γ release assay. Results The seroconversion rate was 47.2%, 100%, 69.4% and 100% one month after the 1st dose, one and six months after the 2nd dose and four months after the heterologous 3rd dose. The median (Q1, Q3) anti-SARS-CoV-2 spike IgG concentrations at the same time were 28.7 (13.2, 69.4) BAU/ml, 1130.0 (594.5, 1735.0) BAU/ml, 89.7 (26.4, 203.8) BAU/ml, and 2080.0 (1062.5, 2080.0) BAU/ml. The percentage of patients with neutralizing antibodies was 58.3% after the 2nd dose and improved to 100% after the 3rd dose (P <0.001). A positive T-cell response was found in 50% of patients after the 3rd dose. Conclusions A third heterologous booster dose helped to sustain humoral immunity in almost all hemodialysis patients and induced a significant T-cellular response in half of them. Stimulating the immune response against SARS-CoV-2 by two different vaccine platforms seems to be a promising approach.